The Influence of Teaching at The Right Level (Tarl) Learning Strategy on Physical Education Learning Outcomes: A Mixed Method Study in Vocational High Schools - Pangestu, Ardian Yoga; Pratama, Dani Slamet (Lembaga Jurnal dan Publikasi Universitas Muhammadiyah Buton, 2025)
TaRL is a learning approach designed to adjust teaching materials to students' abilities, aimed at addressing learning outcome disparities caused by differences in academic and physical capabilities. This study seeks to examine the influence of the TaRL-based learning strategy on learning outcomes in Physical Education, Sports, and Health (PJOK) among secondary school students in Indonesia, where this approach is rarely implemented. The research employed a one-group pretest-posttest design involving 30 tenth-grade students selected through purposive sampling. The research methodology was Mixed-Method. Quantitative data were collected through cognitive and psychomotor tests, complemented by qualitative data from interviews and observations. Research findings demonstrated a significant improvement in student learning outcomes, with the average cognitive score increasing from 82.44 to 93.33 and the psychomotor score rising from 1.80 to 3.13. The TaRL approach facilitates inclusive and meaningful learning experiences, enhancing student motivation and engagement through personalized learning tailored to individual needs. These findings indicate that TaRL is effective in addressing learning gaps and promoting student-centered learning in Physical Education. The study recommends implementing TaRL as an alternative strategy to improve educational practices in Indonesia by encouraging a more inclusive and differentiated curriculum to meet diverse student requirements.